Clinical Outcomes of Posterior Lumbar Interbody Fusion versus Minimally Invasive Transforaminal Lumbar Interbody Fusion in Three-Level Degenerative Lumbar Spinal Stenosis. (26th September 2016) - Fan, Guoxin; Wu, Xinbo; Yu, Shunzhi; Sun, Qi; Guan, Xiaofei; Zhang, Hailong; Gu, Xin; He, Shisheng
Abstract : The aim of this study was to directly compare the clinical outcomes of posterior lumbar interbody fusion (PLIF) and minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) in three-level lumbar spinal stenosis. This retrospective study involved a total of 60 patients with three-level degenerative lumbar spinal stenosis who underwent MIS-TLIF or PLIF from January 2010 to February 2012. Back and leg visual analog scale (VAS), Oswestry Disability Index (ODI), and Short Form-36 (SF-36) scale were used to assess the pain, disability, and health status before surgery and postoperatively. In addition, the operating time, estimated blood loss, and hospital stay were also recorded. There were no significant differences in back VAS, leg VAS, ODI, SF-36, fusion condition, and complications at 12-month follow-up between the two groups (P > 0.05 ). However, significantly less blood loss and shorter hospital stay were observed in MIS-TLIF group (P < 0.05 ). Moreover, patients undergoing MIS-TLIF had significantly lower back VAS than those in PLIF group at 6-month follow-up (P < 0.05 ). Compared with PLIF, MIS-TLIF might be a prior option because of noninferior efficacy as well as merits of less blood loss and quicker recovery in treating three-level lumbar spinal stenosis.